Levantamento, classificação taxonômica e de capacidade de uso dos solos da Estação Florestal Experimental (EFLEX) do IBAMA, Sobral - Ceará - Sena, Antonio Edinardo Soares de (1994)
The main objectives of the present study were: (a) to survey and classify the soils of the area (624.11 ha) of study by using both the brazilian system of soil classification and soil taxonomy, and (b) to determine the land use capability af the soils surveyed which be Long to IBAMA - EFLEX-SOBRAL-CE (Brazilian Agency for Environment Protection). The following geological and environmental characteristics af the area were described: area location, geological features, relief, hydrography/hidrology, drainage systems, climate, vegetation, actual land use, prevailing soil groups, and hydrological balance. Eight soil taxanomic units were identified from the complete description of eight soil profiles in the area of study. By using the brazilian soil classification system, the soils were classified as: Unit Re1 - SOLO LITÓLICO Tb EUTRÓFICO A MODERADO TEXTURA MÉDIA; Unit Re2 - SOLO LITÓLICO Ta EUTRÓFICO A FRACO TEXTURA MÉDIA; Unit NC - BRUNO NÃO CÁLCICO LITÓLICO A MODERADO TEXTURA ARGILOSA; Unit V1 - VERTISSOLO SOLÓDICO A MODERADO; Unit Ae - SOLO ALUVIAL VÉRTICO EUTRÓFICO SOLÓDICO Ta TEXTURA MÉDIA; Unit V2 - VERTISSOLO A FRACO; Unit V3 - VERTISSOLO A MODERADO; Unit PL -PLANOSSOLO SOLÓDICO VÉRTICO Ta A MODERADO TEXTURA MÉDIA/ARGILOSA. By using the soil taxonomy system, the soils were classified as: Units Re1 and Re2 - LITHIC USTIC TORRIORTHENTS; Unit NC - LITHIC USTOLLIC HAPLARGIDS; Units V1, V2 and V3 - TYPIC HAPLOTORRERTS; Unit Ae - USTERTIC TORRIFLUVENTS; Unit PL - VERTIC PALEARGIDS. Concerning the land use capability the following classes and subclasses were identified: Classe V - Subclasses Vc and Va,c (adequate for annual crops, reforestation and/or pasture); Classe VI - Subclasse VIs (adequate for pasture and reforestation); Classe VII - Subclasse VIIs (adequate for reforestation and pasture in a very small scale). The maps were constructed by using aerial photografies in an approximate scale of 1:8000 dated of May, 1976; after interpreting the above cited aerial photographies, the following documents were constructed: the detailed soil map; the land use capability map and the actual land use map; all those maps are in the 1:8000 approximate scale and show the area percentage of all soil units studied.